2016
DOI: 10.1007/s00383-016-3980-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased Act1/IL-17R expression in Hirschsprung’s disease

Abstract: To our knowledge, we report, for the first time, the expression of Act1 in the human colon. The increased expression of Act1 and Il-17 in the aganglionic and ganglionic bowel in HSCR may result in IL-17-mediated increased inflammatory response leading to the development of HAEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…For instance, IL-11 plays an important role in the survival, maturation, and myelin formation of oligodendrocytes. A study by Tomuschat et al reported that the pro-inflammatory cytokines were observed in both the aganglionic and ganglionic and aganglionic regions of the bowels of patients with HSCR [8,9]. A population-based genome-wide association study (GWAS) on the Korean population was performed by Kim et al, showing that a number of SNPs on IL-11 such as rs1126760, rs4252546, and rs8104023 have statistically significant associations with HSCR based on 187 cases and 283 controls [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, IL-11 plays an important role in the survival, maturation, and myelin formation of oligodendrocytes. A study by Tomuschat et al reported that the pro-inflammatory cytokines were observed in both the aganglionic and ganglionic and aganglionic regions of the bowels of patients with HSCR [8,9]. A population-based genome-wide association study (GWAS) on the Korean population was performed by Kim et al, showing that a number of SNPs on IL-11 such as rs1126760, rs4252546, and rs8104023 have statistically significant associations with HSCR based on 187 cases and 283 controls [10,11].…”
Section: Introductionmentioning
confidence: 99%